2008
DOI: 10.1093/toxsci/kfn125
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation Dosimetry Modeling with Decamethylcyclopentasiloxane in Rats and Humans

Abstract: Decamethylcyclopentasiloxane (D(5)), a volatile cyclic methyl siloxane (VCMS), is used in industrial and consumer products. Inhalation pharmacokinetics of another VCMS, octamethylcyclotetrasiloxane (D(4)), have been extensively investigated and successfully modeled with a multispecies physiologically based pharmacokinetic (PBPK) model. Here, we develop an inhalation PBPK description for D(5), using the D(4) model structure as a starting point, with the objective of understanding factors that regulate free bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 21 publications
0
22
0
3
Order By: Relevance
“…This value is slightly larger than the corresponding default parameter in Reddy's dermal PBPK model for D5, which is 0.0055 min −1 and 0.011 min −1 for men and women, respectively (Reddy et al, 2008). The discrepancy may result from the fact that the PBPK model was developed based on human in vivo data (Plotzke et al, 2002), whereas our estimations were derived from in vitro experiments with porcine skin.…”
Section: Chamber Experiments With Porcine Skin In Vitromentioning
confidence: 74%
“…This value is slightly larger than the corresponding default parameter in Reddy's dermal PBPK model for D5, which is 0.0055 min −1 and 0.011 min −1 for men and women, respectively (Reddy et al, 2008). The discrepancy may result from the fact that the PBPK model was developed based on human in vivo data (Plotzke et al, 2002), whereas our estimations were derived from in vitro experiments with porcine skin.…”
Section: Chamber Experiments With Porcine Skin In Vitromentioning
confidence: 74%
“…As previous studies indicated that inhalation F uptake for D4 and D5 was about 0.1 due to their low blood/air partition, 16,17 our study selected 0.1 as inhalation F uptake for cyclic compounds (D4−D6). Due to lack of specific F uptake for linear compounds, 1.0 was selected as F uptake for L3−L16.…”
Section: Methodsmentioning
confidence: 99%
“…Several groups have measured methyl siloxane concentrations in human plasma in controlled human exposures, such as the reports on octamethylcyclotetrasiloxane (D4) and decamethylcyclopentasiloxane (D5) concentrations in plasma after 1-h exposures via inhalation (122 and 153 μg/L for D4 and D5, respectively.) 16,17 However, to our knowledge, there are no reports on methyl siloxane concentrations in the plasma of general or highly exposed populations in P.R. China or other countries.…”
Section: Introductionmentioning
confidence: 95%
“…The resulting 14 C-labeled siloxanes (for example, octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane, dodecamethylcyclohexasiloxane, hexamethyldisiloxane, poly(dimethylsiloxanes) of various viscosities, etc.) are routinely utilized as tracers in environmental and toxicological investigations [2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%